Symbolika ratuszy w przestrzeni miasta średniowiecznego. Wybrane przykłady - Eysymontt, Rafał (Roczniki Dziejów Społecznych i Gospodarczych, 2014)
The symbolism of town halls in medieval cities. Selected examples (Summary) Town halls have always been the best example of the aspirations and possibilities of urban communities. The location of the town hall building was related to its central role in the political system and functioning of the town. This was the case, irrespective of the period in which the building was raised, or its size. Its functional and ideological centrality in the urban space was achieved in several ways. The first, dating back to the ancient tradition, is associated with the classical structure of a city based on a rectilinear grid of streets – the town hall takes the place of the Roman praetorium, which was in the castrum at the intersection of the cardo and decumanus. This was not only the case in cities in the Apennine Peninsula, but also in colonized areas – in the towns established on the former sites of Roman camps. If the town hall building was part of a densely developed area, its form always distinguished it from the other buildings, and if it was a free-standing building, it competed with the church buildings with regards to its shape and location. Another way of emphasizing the central role of the main municipal building in the urban layout was to make it the main vertical accent, by accentuating its height with regard to the church towers – as in the solutions associated with the Flemish idea of the beffroi. The third important aspect regarding the spatial composition of medieval cities was the location of the town hall building in close relation to the “dynamic” diagonal axis of the town’s layout linking the town hall with the cathedral or parish church. This kind of layout can be found both on the Apennine Peninsula and in Silesia. The signifi cant analogies, which are visible at first glance, between the functioning of various town hall buildings in various geographical regions far away from one another, confirm the appropriateness of undertaking further research on the various groups of buildings in urban layouts both in the context of contemporary ideas and archetypes that had an influence throughout the whole of Europe, which in this context appears to be a culturally homogenous area.